Androgenic and estrogenic indices in human newborns and infants: the MIREC-ID study. (11th March 2019) - Nguyen, T-V.; Monnier, P.; Muckle, G.; Sathyanarayana, S.; Ouellet, E.; Velez, M. P.; Dodds, L.; Arbuckle, T. E.
Abstract: Prenatal sex steroid exposure plays an important role in determining child development. Yet, measurement of prenatal hormonal exposure has been limited by the paucity of newborn/infant data and the invasiveness of fetal hormonal sampling. Here we provide descriptive data from the MIREC-ID study ( n =173 girls; 162 boys) on a range of minimally invasive physical indices thought to reflect prenatal exposure to androgens [anogenital distances (AGDs); penile length/width, scrotal/vulvar pigmentation], to estrogens [vaginal maturation index (VMI) – the degree of maturation of vaginal wall cells] or to both androgens/estrogens [2nd-to-4th digit ratio (2D:4D); areolar pigmentation, triceps/sub-scapular skinfold thickness, arm circumference]. VMI was found to be associated with triceps skinfold thickness (β=0.265, P =0.005), suggesting that this marker may be sensitive to estrogen levels produced by adipose tissue in girls. Both estrogenic and androgenic markers (VMI: β=0.338, P =0.031; 2D:4D – right: β=−0.207, P =0.040; left: β=−0.276, P =0.006; AGD-fourchette − β=0.253, P =0.036) were associated with areolar pigmentation in girls, supporting a role for the latter as an index of both androgen and estrogen exposure. We also found AGD-penis (distance from the anus to the penis) to be associated with scrotal pigmentation (β=0.290, P =0.048), as well as right arm circumference (β=0.462, P <0.0001), supporting the notion that these indices may be used together as markers of androgen exposure in boys. In sum, these findings support the use of several physical indices at birth to convey a more comprehensive picture of prenatal exposure to sex hormones.